Language Melody, Islamic Harmony: The Role of Indonesian Language Teachers in Creating Inspiring Islamic Schools - Tengku Aldy Hatta; Indah Purnama Sari; Putri Rizki Syafrayani (EDUCATION JOURNAL OF INDONESIA, 2024)
This research aims to answer the problem of how to become an inspirational teacher in the learning process in class. This research uses a descriptive qualitative approach to schools Al-Azhar ash-sharif North Sumatra. Based on data analysis, research results show that there are several initial things What teachers at the Al-Azhar Asy-Syarif Islamic School in North Sumatra need to do are (1) ensure the class setting is interesting and support inspirational learning (2) carry out a Needs Assessment to ensure that the material is appropriate delivered to arouse high awareness among students (3) Inspirational Lesson Plan or RPP planning (4) The implementation process is in accordance with planning and (5) ensures that there is an evaluation of the learning process so that there will be continuous improvement. The steps above are based on an approach that focuses on Inspirational spirit, in which several North Sumatra Al-Azhar Asy-Syarif teachers who were research subjects had confidence holds the view that (1) students are inspirational triggers (2) Teachers must be inspirational (3) Design empowering curriculum (4) creative learning methods and (5) organizing inspiring classes. Specifically, inspiring learning methods require active, innovative, creative, effective and fun. Based on the analysis and research findings, it is recommended to the Al-Azhar Asy-Syarif School to carry out a culture of study lessons between teachers in order to create enthusiasm to continue to be inspirational teachers for their students. Keyword : Inspirational Teachers, Learning Process and Learning Paradigms.